ANALYSIS OF CYLINDER HEAD REPAIR OF MAIN ENGINE: A CASE STUDY OF PASSENGER SHIP KM GD IN INDONESIA - Ariany, Zulfaidah; Zaida , Khayeisa Alzena; Zhixun, Zhang (Journal of Applied Engineering Science, 2025)
KM GD a passenger ship operated by PT. PELNI. Playing an important role as a transportation link between regions in Indonesia, especially given the country’s archipelagic geography. The reliability of the main engine as the main driver of the ship is a crucial factor in ensuring smooth operations. One of the vital components in a master engine system is the cylinder head at KM GD was found to have repeated damage to the cylinder head shortly, although repairs have been made. Damage to the cylinder head has a high presentation on engine operation. Repeated damage is interesting for research to discover more details about the causes of cylinder head cracks. This study identified the root cause of damage using the Root Cause Analysis method with the 5 Whys approach and the Fishbone diagram. The results of the study show that many factors are the cause of cracks. The main factor of damage is a non-standard reconditioning procedure. Repairs to standards provide significant savings and improve engine reliability. Research using the RCA method effectively analyses technical issues and supports efficient and sustainable treatment decision-making. Recommendations are given to improve the working performance of the machine after reconditioning, among others, through the implementation of strict technical procedures according to the manufacturer's standards and increased quality control during the repair process. With a thorough improvement in this technical and managerial aspect, it is hoped that the damage frequency can be reduced and the reliability of the main's engine can be optimally maintained to support operations KM GD.
Keywords: cylinder head, root cause analysis, recondition, main engine, passenger ship